Environmental safety of boron compounds in cellulose insulation - Dubatouka, Anton I. (Journal of the Belarusian State University. Ecology, 2019)
Cellulose insulation (CI) of domestic manufacturers contains additives of boron compounds in large quantities. A review of the literature on the safety of the use of the CI in the course of its life cycle was conducted. On the basis of data from foreign studies, was made an assessment of the possibility of exceeding the maximum allowable concentration of boron compounds when working with the CI and its operation. Taking into account domestic realities it is recommended to conduct a study on the environmental safety of the life cycle of CI.